Pengembangan Chatbot “Ciovita” Virtual Assistant Cioccolato Brownie Semarang Dengan Metode Waterfall - Elita Natalia Sugianto; Jessica Aurelia Sujangga; Novita Delvia; Verdiana Ayustika; Agus Cahyo Nugroho (Indonesian Society of Applied Science, 2022)
Cioccolato brownie is a business engaged in the food business, namely brownies. In doing business, Cioccolato brownie performs the traditional process of presenting information to consumers to obtain product and development information. Where by contacting and communicating through the admin or business owner via short messages. Therefore, consumers will take a long time to get the desired business or product information. Meanwhile, business owners or admins also become inefficient and inefficient in running a business, because they must be effective in sending messages that may be carried out between one consumer and another. Therefore, to overcome the problems faced by Cioccolato brownie, a virtual assistant chatbot based on website, line and telegram was created. A virtual assistant chatbot named Ciovita. The method used in the development of a virtual assistant with the Waterfall Model is modeled with Usecase, activity diagram and sequence. The final result of the development of this virtual assistant chatbot is a website, line and telegram that can facilitate the provision of product information on Cioccolato brownie, so that it will help Cioccolato brownie in carrying out its business activities more effectively and efficiently.